Polusi Udara di Kawasan Industri Nikel di Morowali: Dampak, Resiko, dan Solusi Mitigasi - Naprida, Alifah Risa; Fikri, Alip Musaqo; Ash Shiddiq, Abdul Malik; Sari, Alya Sirena; Praseliya, Mila; Ulya, M. Ridho (Al-Ard: Jurnal Teknik Lingkungan, 2025)
The nickel industry in Morowali, Central Sulawesi, makes a significant contribution to the regional economy but also causes considerable air pollution problems. Mining, processing, and smelting activities release hazardous emissions such as PM10, PM2.5, sulfur dioxide (SO₂), and dust particles that threaten air quality and public health. The findings show that nickel pollutant concentrations in the IMIP area range from 0.05–0.15 μg/Nm³, exceeding the standard limit of 0.03 μg/Nm³. In addition, SO₂ concentrations reached 288.497 μg/m³, far above the standard of 150 μg/m³. Health impacts are reflected in the surge of Acute Respiratory Infection (ARI) cases at Bahodopi Health Center, increasing from around 10,000 cases in 2020 to 55,527 cases by January 2023. Although mitigation efforts through government regulations and the implementation of environmentally friendly technologies have been carried out, pollution levels remain high. This study recommends the application of Baghouse Filter technology as a primary solution to reduce particulate emissions by up to 99.9%. Collaboration between industry, government, and communities is essential to achieve sustainable solutions.